حماية الأمن الأنساني من تغير المناخ في الأتفاقيات الدولية - عزيز, أ.م.د. بيشره و حمه جان; أحمد, طالب ماجستیر: ميران قادر (Sulaimani Journal for Humanities, 2023)
Although climate change is seen as one of the most prominent security problems in this century, while the subject has so far received little systematic analysis as a security issue, so we try through this study to explore systematically the scope of the interrelationship between climate change and security, Including human security considerations and concerns, while addressing and discussing the role that international solutions and remedies represented by international agreements can play in reducing its harmful effects and mitigating its repercussions on human security dimensions. We also discuss this study in issues related to both mitigation and adaptation to change The climate proposed by the international community in order to provide legal mechanisms to protect the climate system as a prerequisite for human protection and self-security.